Mislocalization of sensory information in people with chronic low back pain: A preliminary investigation - Wand, B.; Keeves, J.; Bourgoin, C.; George, P.; Smith, Anne; O'Connell, N.; Moseley, G. (Lippincott Williams & Wilkins, 2013)
Objectives: The purpose of this study was to establish if people with chronic low back pain (CLBP) demonstrate impairments in the ability to localize sensory information delivered to the back more than pain-free controls and determine whether any sensory abnormalities are related to pain-related variables.Methods: Vision was occluded and participants were stimulated using light touch or pinprick over a number of body areas in random order. To assess for mislocalizations participants were asked to nominate the location of each stimulus in reference to a marked body chart. To assess referred sensations participants who were asked whether they experienced any sensations elsewhere during stimulation. If referred sensations were reported, testing was repeated with visualization of the stimulated area.Results: Although a small number of CLBP patients demonstrated referral of sensations, this was not statistically different from what was observed in a pain-free control group (P=0.381). In contrast, mislocalizations were very common in the patient sample and statistically more common than we found in controls (P=0.034). No statistically significant associations were detected between sensory function and the measured pain-related variables (all P>0.05).Discussion: These data add to a growing body of evidence suggesting that disturbed self-perception is a feature of CLBP. It is plausible that altered self-perception is maladaptive and contributes to the maintenance of the problem and may represent a target of treatment for CLBP.